Role of Fetal Cardiac ECHO and Fetal Cardiac MRI in Prediction of Post Natal Hemodynamic Maladaptation in Fetuses of Diabetic Mothers - Mohamed Ahmed, Sara Mahfouz; EL Ganzory, Mona Mosatafa; Mamdouh Habeeb, Nevin Mohamed; El Sayed, Eman Mohamed; Mohammed Ali, Hend Galal Eldeen; Abd Elaal, Mohamed Omar (International Journal of Child Health and Nutrition, 2024)
Background: Maternal diabetes mellitus (DM) is defined as a degree of glucose intolerance with recognition during pregnancy (pregestational or gestational, type 1 or type 2), and it is estimated to be 15% in pregnant females in 2019. The current study aimed to study the role of fetal echocardiography and fetal cardiac magnetic resonance imaging (MRI) in anticipation and diagnosis of hemodynamic maladaptation changes in fetuses of diabetic mothers as predictors for (closure of Patent ductus arteriosus (PDA), persistent pulmonary hypertension and diastolic dysfunction) which were confirmed with post-natal echocardiographic and clinical assessment. Methods: This study was an observational follow-up study that included 80 pregnant diabetic females who were following in the specialized clinics of Ain Shams University Hospitals during the period starting from August 2020 till December 2022. Results: Diabetes affected left ventricle (LV) diastolic function and global cardiac function but did not affect LV systolic function (p-value=0.000). Interventricular septum (IVS) thickness had a significant positive correlation with LV- Myocardial performance index (MPI) and indices of DM such as HbA1c. Diastolic dysfunction was the most affected cardiac parameter in infants of diabetic mothers (p-value=0.002). The hemoglobin A1c (HbA1c) was the most significant predictor for IVS thickness in diabetic mothers' fetuses, especially with a long duration of DM (p-value=0.012). Conclusion: Fetal echocardiography in diabetic mothers is essential and the gold standard modality not only for diagnosing structural abnormalities but also for evaluating the cardiac function of the fetuses. Fetal cardiac MRI could be considered a complementary imaging modality that uses no ionizing radiation, good tissue contrast, and a larger field of view.